Lactobacillus reuteri associated with scaling and root planing in the treatment of periodontitis in rats submitted to chemotherapy - Miessi, Daniela Maria Janjácomo [UNESP] (2020)
Objective: The aim of this study was to evaluate the effects of Lactobacillus reuteri applied locally or systemically with scaling and root planing (SRP) to the treatment of experimental periodontitis (EP) in rats treated with 5-fluorouracil. Methods: A cotton ligature was installed on the molars of rats. The animals (n = 54) underwent chemotherapy and were divided into groups: SRP (n = 18), scaling and root planing only; LP (n = 18), SRP and 4 sessions of local probiotic (PRO); SP, SRP and 4 sessions of systemic PRO. The molar furcation area was submitted to histopathological, histometric of alveolar bone loss (ABL) and immunolabeling analysis after euthanasia at 7, 15 and 30 days. The data were submitted to statistical analysis (α = 5%). Results: At 15 days ABL was higher in LP compared to SP. At 30 days, ABL was higher in LP compared to SRP and SP. Higher immunolabeling of TGF-β1 was observed in LP and SP at 7 days compared to SRP (p < 0.05). Lower immunolabeling of OCN and higher immunolabeling of RANKL were observed at all periods in SRP compared to SP (p < 0.05). At 30 days, SRP showed lower immunolabeling of OPG compared to SP and LP (p < 0.05). In SP, lower immunolabeling was observed at 15 days compared at 30 days (p < 0.05). Conclusion: The ABL was similar among the groups treated with SRP associated or not to probiotic therapeutic, although the systemic use of Lactobacillus reuteri considerably reduced inflammation and favored periodontal tissues repair.